Selecting Nonpharmaceutical Strategies to Minimize Influenza Spread: A Comprehensive Review - Fatimah Ibrahim Alkhsrs et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Influenza poses a significant global health burden, with seasonal epidemics causing millions of cases annually. While vaccination and antiviral treatments remain essential tools in combating influenza, nonpharmaceutical interventions (NPIs) play a critical role in reducing its spread, particularly during pandemics or vaccine shortages. This review examines the efficacy, challenges, and implementation strategies of NPIs, including social distancing, mask usage, hand hygiene, school closures, and quarantine. Emphasizing evidence from recent outbreaks, it highlights the importance of coordinated public health efforts and community engagement in mitigating influenza transmission. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/302 DOI: https://doi.org/10.5281/zenodo.14596474